Changes in the intestinal microbiota of patients with Parkinson’s disease and their clinical significance - Zhang, Li-Na; Yuan, Wen-Ling; Ye, Ming; Yin, Liang; Wang, Shi-Jie (International journal of clinical pharmacology and therapeutics, 2023)
To investigate the differences and their clinical significance in the intestinal microbiota in patients with Parkinson's disease (PD) in comparison to those in healthy controls. 20 patients with PD who received treatment in the First Affiliated Hospital of Bengbu Medical College between January 2019 and December 2019 were selected as the research subjects to form the PD group, while 20 age- and gender-matched healthy volunteers were selected as the control group. Fecal samples from the two groups were collected, and the V4 region of 16S-ribosomal ribonucleic acid was selected for high-throughput sequencing analysis to explore any differences, as well as their significance, in the intestinal microbiota abundance at the class, family, and genus levels between the two study groups. The operational taxonomic unit cluster analysis revealed a high degree of overlap between the patients with PD and the controls. Compared with the controls, the relative abundance of and was increased in the PD group (p < 0.01), while the relative abundance of was significantly lower (p < 0.01). The relative abundance of , , and in the PD group was significantly higher than in the control group (p < 0.05). Compared with the healthy subjects, the abundance of specific microflora was significantly different in the PD patients at the class, family, and genus level. Intestinal flora may act as a potential biomarker for PD and provide a theoretical basis for microflora transplantation therapy.